Labor Turnover and the Natural Rate of Unemployment: Efficiency Wage versus Frictional Unemployment. - MacLeod, W; Malcomson, J; Gomme, P (1994)
Wage and unemployment responses to changes in economic environment are compared for efficiency wage and frictional models. Changes in aggregate demand, persistence of job-specific shocks, cost of living, and unemployment benefits are considered. Wages and unemployment move in the same direction in the two models, except that an upward shift in aggregate labor demand can reduce the real wage in the efficiency wage, but not the frictional, model. In a numerical simulation calibrated to U.S. data, real productivity shocks in the efficiency wage model yield a ratio of unemployment to wage variability close to that of the United States.